Hunger in Holland : life during the Nazi occupation - Fuykschot, Cornelia 1929- (Prometheus Books, 1995)
This compelling first-person account is an eye-opening depiction of life in occupied Holland during World War II. As a twelve-year-old girl, Cornelia Fuykschot experienced the invasion of her country by the Germans and the resulting loss of freedom, scarcity of food, and steady deterioration of normal, everyday life. Fuykschot describes how she and her family were forced to adapt to the conditions of a police state. Though still a child, she took on the responsibility of begging for food and helping to hide her father from the Nazis, who had shipped every man they could find to the munitions factory to work for the German war effort. Fuykschot vividly illustrates the strength, ingenuity, and dogged determination of ordinary people struggling to maintain some semblance of normalcy against a backdrop of bombing raids and daily Nazi terrorism. Hunger in Holland is a moving chronicle of a horrifying period in world history, a testament to both survivors and victims, and a valuable lesson for those who have never known the terror of war.